Exuberant Praise: A Pentecostal Reading of Psalm 150 - Lee Roy Martin (Pharos Journal of Theology, 2022)
Enthusiastic praise of God has been a vital characteristic of the Pentecostal movement, and Pentecostals have appealed to Psalm 150 as justification for their extravagant worship. Therefore, the methodology of this article views Psalm 150 through the lens of Pentecostal spirituality and offers a contemporary appropriation of this biblical text for contemporary worship. The methodology includes historical–grammatical exegesis that focuses on the rhetorical effect of the poetic structure and content. The psalm is examined in light of its theology of worship, its role as the final song in the Psalter, and its implications for Pentecostal worship. The wide variety of musical instruments named in Psalm 150 suggests that any and all kinds of instruments can be used in worship. Colonialistic restrictions on instruments should be avoided. Many contemporary Pentecostal congregations have adopted a concert-like approach, in which everyone’s attention is directed toward the stage, where professional musicians enact a performance of praise. The instruments found in Psalm 150, however, include those that are played by the non-professionals, whom we would call the laity. Furthermore, participative community is implied in the invitation for “every breath” to praise the Lord.